Edição do gene PD-L1 modula proliferação e resposta a quimioterápicos em modelo celular de câncer de próstata - Manso, Mariana Palmeira (2025)
Immunotherapy based on immune checkpoint inhibitors, such as those acting on the PD-1/PD-L1 axis, has been widely used in various types of tumors. Overexpression of PD-L1 (programmed death-ligand 1) in cancer cells inhibits the activation and proliferation of T lymphocytes by interacting with the PD-1 (programmed cell death protein 1) receptor, favoring immune evasion. In metastatic castration-resistant prostate cancer (mCRPC), anti-PD-L1 monotherapy has limited efficacy, although combinations with other agents show benefits in advanced tumors and/or those with a high mutational burden. Despite the clinical impact in other tumors, the compensatory mechanisms related to the action of PD-L1 in prostate cancer have been little explored, as have the mechanisms of resistance and tumor survival. In this study, PD-L1 gene editing in mCRPC cells (DU-145) was performed using the CRISPR/Cas9 technique, with the use of in silico validated sgRNA. The edited cells (PD-L1⁻) were evaluated by flow cytometry and separated by sorting. PD-L1 editing was confirmed by Sanger sequencing and quantitative PCR. The effects of editing were analyzed based on the protein profile by mass spectrometry, cell proliferation, and the MTT assay to analyze the response to chemotherapeutic agents (doxorubicin, paclitaxel, cabazitaxel, and docetaxel) and the experimental compound +(-)PTC. In sequencing, thymine addition was observed at position 274, and the relative expression of PD-L1 in the edited lineage was reduced by ~50% (p<0.005) compared to the unedited lineage (2.5). The PD-L1⁻ lineage showed slower duplication (62h30min) compared to PD-L1⁺ (33h27min). Among the proteomics results, proteins associated with increased tumor proliferation and metabolism were found to be negatively regulated, such as EIF5B, PSAT1, PKG1, GOT2, and SHMT2. MTT assay data showed different IC50 values between the PD-L1⁺ and PD-L1⁻ lines, respectively: i) doxorubicin: 403.5 nM and 173.8 nM; ii) paclitaxel: 28.56 nM and 8.32 nM;iii) docetaxel: 4,57 nM and 7,97 nM; iv) cabazitaxel: 9.93 nM and 18 nM; and (v) +(-)PTC:13.54 µM and 23.36 µM. The EC50 values of the compounds doxorubicin, paclitaxel, and+(-)PTC were statistically significant, with p < 0.05. PD-L1 gene editing was effective, promoting reduced proliferation, altered protein profile, and modulation of drug response, suggesting the need to investigate the mechanisms of tumor resistance related to this checkpoint.